Rolling contact fatigue behavior of dual-phase austempered ductile iron - Colombo, Diego Alejandro (2019)
In this work the rolling contact fatigue (RCF) behavior of dual-phase austempered ductile iron (ADI) was studied and compared to that of conventional ADI. The effect of surface finishing (manual vs. automatic grinding) on the surface properties and RCF endurance was also analyzed. RCF tests were performed in a flat washer type testing rig and using lubricated pure rolling conditions. RCF tests results were analyzed using the two-parameter Weibull distribution and the Weibayes method. The results indicated that the dual-phase ADI metal matrix was composed of 94% ausferrite and 6% free allotriomorphic ferrite, approximately. The hardness of conventional ADI was higher than that of dual-phase ADI. The residual stresses were compressive in all the cases with similar average values for ADI and dual-phase ADI. Relative to manual grinding, the automatic process increased slightly the surface hardness and reduced by around a 50% the residual stresses of both ADI and dual-phase ADI. Regarding RCF, failures were characterized by the typical concentrated damage in the form of spalls. No significant differences in the RCF endurance of ADI and dual-phase ADI were observed. No differences in the RCF endurance attributable to the surface finishing method were identified in the current tests.